Medical comorbidity in complicated grief: Results from the HEAL collaborative trial. (January 2018) - Robbins-Welty, Gregg; Stahl, Sarah; Zhang, Jun; Anderson, Stewart; Schenker, Yael; Shear, M. Katherine; Simon, Naomi M.; Zisook, Sidney; Skritskaya, Natalia; Mauro, Christina; Lebowitz, Barry D.; Reynolds, Charles F.
Abstract: Objective: To describe medical comorbidity in persons with Complicated Grief (CG) and to test whether medical comorbidity in individuals with CG is associated with the severity and duration of CG, after adjusting for age, sex, race, and current depressive symptoms. Methods: In exploratory analyses, we compared data from participants in an NIMH-sponsored multisite clinical trial of CG ("HEAL": "Healing Emotions After Loss") to archival data from participants matched on age, gender, and race/ethnicity, stratified by the presence or absence of current major depression. We used the Cumulative Illness Rating Scale for Geriatrics (CIRS-G) as a measure of medical polymorbidity. We investigated the association between CG and medical comorbidity via multiple linear regression, adjusting for sociodemographic and clinical variables, including severity of depressive symptoms. Results: Chronological age and severity of co-occurring symptoms of major depression correlated with cumulative medical polymorbidity in persons with Complicated Grief. The severity of CG and the time since loss did not correlate with global medical polymorbidity (CIRS-G score). Nor was there an interaction between severity of depressive symptoms and severity of CG symptoms in predicting global CIRS-G score. Cumulative medical comorbidity, as measured by CIRS-G scores, was greater in subjects with current major depression ("DEPRESSED") than in CG subjects, and both DEPRESSED and CG subjects had greater medical morbidity than CONTROLS. Conclusion: Medical comorbidity is prevalent in Complicated Grief, associated with increasing age and co-occurring depressive symptoms but apparently not with chronicity and severity of Complicated Grief per se. This observation suggests that treating depression in the context of CG may be important to managing medical conditions in individuals with Complicated Grief to attenuate or prevent the long-term medical sequelae of CG.